Peran Guru Agama Islam dalam Pembentukan Karakter Siswa - erdiyah, elva (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2025)
A character is something that every person on this earth has while they are still alive. However, sometimes a person's character can be different from one another, some people have good character and some have bad character. Sometimes, a person's character can be a genetic inheritance from their parents or social factors, environment and character is also a trait that is very attached to a person, so it can be said that sometimes it is quite difficult to change it with just a command, but this also requires support and desire. yourself to change. An Islamic religious teacher is a human being. Therefore, this is where the importance of an Islamic teacher in school is so that they can be a role model for their students because in the current era of globalization, many students' characters are starting to be eroded by time and influenced by technology. As a religious teacher, we must be able to become a figure that our students can emulate so that they can form good character in their students and ultimately commendable morals (character) are engraved in their souls.